A Personality Study Of The Main Character In Luca Movie - Lestari, Dian Ayu; Winarta, Ida Bagus Gde Nova (Institut Pariwisata dan Bisnis Internasional, 2025)
Nowadays we can meet people with various types of personality that are diverse and sometimes unique. Therefore, this research entitled